Collisional broadening of oxygen fine structure lines: The impact of temperature. (January 2016) - Koshelev, M.A.; Vilkov, I.N.; Tretyakov, M.Yu.
Abstract: The temperature dependence of self-, nitrogen- and air-broadening coefficients of oxygen fine structure lines was studied. Temperature exponents of a series of oxygen lines with rotational quantum number N ranging from 1 to 19 were measured with high accuracy for the first time. The obtained parameters were compared with the results of the earlier studies. This information is of high importance for atmospheric applications. Highlights: Temperature dependence of the oxygen fine structure line widths was studied. Rotational dependence of the temperature exponents was analyzed. Results were compared with earlier experiments. Pressure shifts were found to be negligible.